1999
DOI: 10.1111/j.1574-6968.1999.tb13560.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of induction of virulence factor expression by activated charcoal inListeria monocytogenes

Abstract: Activated charcoal has been previously shown to induce in vitro expression of virulence factors by Listeria monocytogenes. In trying to elucidate the nature of the charcoal action, we found that the treatment of brain heart infusion medium with activated charcoal followed by charcoal removal does not result in an increase of virulence factor expression. At the same time, the addition of fresh charcoal to the charcoal-treated medium induces expression, suggesting that the effect of activated charcoal cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 10 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…L. monocytogenes were routinely cultivated in the Brain Heart Infusion (BHI, BD, USA) medium. To get a virulence regulon induction, L. monocytogenes was grown in BHI supplemented with 0,2% activated charcoal (Merck) [ 26 ]. E. coli used in cloning and expression procedures were cultivated in the LB medium (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…L. monocytogenes were routinely cultivated in the Brain Heart Infusion (BHI, BD, USA) medium. To get a virulence regulon induction, L. monocytogenes was grown in BHI supplemented with 0,2% activated charcoal (Merck) [ 26 ]. E. coli used in cloning and expression procedures were cultivated in the LB medium (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…To test if metal ions can negate the effect of activated charcoal on the expression of hly and actA in BHI medium, GFP fluorescence levels were measured in L. monocytogenes cells expressing either P hly -eGFP or P actA -eGFP and grown in AC-BHI medium supplemented with iron, zinc, or both (S1 Fig) . While addition of zinc to AC-BHI medium marginally but significantly reduced the expression of P hly -eGFP, addition of iron or iron and zinc had no significant effect on the expression of P hly -eGFP (S1A Fig). Furthermore, addition of iron, zinc or both had no significant effect on P actA -eGFP expression in AC-BHI (S1B Fig) . However, it is important to note that the activated charcoal in AC-BHI medium may continuously chelate metal ion [36,49], negating the effect of metal ion addition, which could explain the limited effect of metal ion addition on hly and actA expression found here. Pre-treatment of BHI with activated charcoal and its subsequent removal by filtration, in a similar manner to Chelex pretreatment, was not feasible since it has been shown that pre-treatment of BHI with activated charcoal was not sufficient to induce PrfA-dependent gene expression and that activated charcoal must be present throughout the course of bacterial growth [36,37].…”
Section: Plos Onementioning
confidence: 75%
“…Furthermore, addition of iron, zinc or both had no significant effect on P actA -eGFP expression in AC-BHI (S1B Fig) . However, it is important to note that the activated charcoal in AC-BHI medium may continuously chelate metal ion [36,49], negating the effect of metal ion addition, which could explain the limited effect of metal ion addition on hly and actA expression found here. Pre-treatment of BHI with activated charcoal and its subsequent removal by filtration, in a similar manner to Chelex pretreatment, was not feasible since it has been shown that pre-treatment of BHI with activated charcoal was not sufficient to induce PrfA-dependent gene expression and that activated charcoal must be present throughout the course of bacterial growth [36,37]. To rule out a possible effect of excess metal ions in the medium on GFP fluorescence per se, we measured P hly -eGFP levels in BHI with increasing iron and zinc concentrations.…”
Section: Plos Onementioning
confidence: 75%
See 2 more Smart Citations